PENERAPAN PENDEKATAN CONTEXTUAL TEACHING LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 011 KEPENUHAN - Ermayuli Ermayuli; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve student’s learning outcomes inmathematics through the application Constextual Teaching and Learning (CTL)approach in the fifth grade students of SDN 011 Kepenuhan. The low yield in the fifthgrade students of SDN 011 Kepenuhan in mathematics due to the lack of preciseapproach or learning model used in the learning process, so that the students' lack ofinterest in participating in the learning of mathematics. The subjects were students ofclass V with a number of all students is 20 people consisting of 8 men and 12 women.The data analyzed in this study is the activity of the teacher, student activities andstudent learning outcomes. Results of data analysis obtained by the percentage of theactivity of teachers at the first meeting of the first cycle of 75% with the good category,the second meeting of the first cycle of 82.1% with the good category and at the firstmeeting of the second cycle percentage teacher activity 85.8% with very good category,the second meeting of the cycle II percentage teacher activity is 92.9% with very goodcategory. At the first meeting of the percentage of student activity 60.7% with enoughcategories, the second meeting of the first cycle is 67.9% with enough category and thefirst meeting of the second cycle the percentage of student activity 82.1% with the goodcategory, the second meeting of the second cycle is 89 , 3% with very good category.And the classical completeness students on the base score is 40% declared incomplete,the first daily test classical completeness of students is 65% stated not yet complete, andthe second daily test classical completeness of students was 100% and otherwisecompleted. Based on this study concluded that the application of learning modelsConstextual Teaching and Learning (CTL) approach can improve students'mathematics learning outcomes.Keywords : Constextual Teaching and Learning (CTL) approach mathematics, learningoutcomes